2016
DOI: 10.7287/peerj.preprints.1728v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitonucleons formed during differentiation of Ishikawa endometrial cells generate vacuoles that elevate monolayer syncytia: Differentiation of Ishikawa domes, Part 1

Abstract: In 1998, we published a paper (Fleming et.al, 1998) describing some aspects of Ishikawa endometrial epithelial cell differentiation from monolayer cells into cells forming fluid-filled hemispheres called domes. The process begins with the dissolution of membranes within discrete regions of the monolayer. Nuclei from fused cells aggregate and endogenous biotin in particulate structures assumed to be mitochondria increase throughout the resulting syncytium. Endogenous biotin is also the distinguishing feature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…An early distinguishing characteristic of dome-forming Ishikawa syncytia is a dramatic increase in the number of mitochondria as detected by streptavidin peroxidase binding to the endogenous biotin of mitochondrial enzymes. Figure 1(a) shows a syncytium within the first 4 hours after initiation of dome formation as previously described [4]. Most of the biotin stain is associated with particulate structures, but it is also possible to detect a transparent membrane staining for biotin wrapped around a nuclear aggregate.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…An early distinguishing characteristic of dome-forming Ishikawa syncytia is a dramatic increase in the number of mitochondria as detected by streptavidin peroxidase binding to the endogenous biotin of mitochondrial enzymes. Figure 1(a) shows a syncytium within the first 4 hours after initiation of dome formation as previously described [4]. Most of the biotin stain is associated with particulate structures, but it is also possible to detect a transparent membrane staining for biotin wrapped around a nuclear aggregate.…”
Section: Resultssupporting
confidence: 52%
“…The biotin stain in domes has also been shown to be associated with mitochondrial enzymes containing biotin [3], demonstrating that the intimate association of fused mitochondria with chromatin early in differentiation likely explains the existence of "intranuclear inclusions" in endometrium and in cancer [10]. tures that could arise from activity of electron transport elements [11] engaged perhaps in anaerobic metabolism in the fused mitochondria creating the gas vacuoles that pressure a chromatin bolus [4]. In a previous paper, it was shown that the formation of the large central gaseous vacuole begins with the merging of multiple gas vacuoles within the fused mitochondria early in the process [12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations